Main wood chemical constituents of Ceiba pentandra, Hevea brasiliensis and Ochroma pyramidale - Honorato-Salazar, J. Amador; Colotl-Hernández, Gertrudis; Apolinar-Hidalgo, Flora; Aburto, Jorge (Instituto de Ecología, A.C., 2016)
In this study, the main wood chemical composition of Ceiba pentandra, Hevea brasiliensis and Ochroma pyramidale was determined with the aim of providing knowledge on wood chemistry of tropical species and information to explore possible chemical applications. For this, the contents of ash, ethanol-benzene extracts, ethanol extracts, lignin, holocellulose, cellulose and hemicelluloses were quantified in the stem at three height levels (bottom, middle, and top). Results of the chemical analysis showed that concentrations of the determined constituents varied within the stem of the individual wood species and also among species. The average amount of chemical compounds among the species was 0,44% - 1,64% for ash; 1,42% - 3,42% for ethanol-benzene extracts; 1,88% - 5,07% for ethanol extracts; 3,83% - 8,46% for total extracts; 19,71% - 26,83% for lignin, 77,73% - 83,52% for holocellulose; 39,67% - 47,63% for α-cellulose and 33,79% - 42,85% for hemicelluloses. According to the obtained contents of lignin, α-cellulose and hemicelluloses, the wood of these species could be used in pulping and bioconversion processes.